Counter Narrative: Dr. Charles S. Johnson’s influence on Myles Horton and Highlander - Catherine H. Monaghan (Adult Education Research Conference, 2014)
This research examines the role of a prominent 20th Century sociologist, Dr. Charles S. Johnson on Myles Horton. It uncovers a connection in the field of adult education between the work of Dr. Johnson and Myles Horton. It pays tribute to Dr. Johnson’s important influence on the work of Highlander.